Electrical and Optical Characterization of Thermally Evaporated Titanyl Phthalocyanine Thin Films - SEBASTIAN, JOSEPH; MENON, C.S. (Asian Journal of Chemistry, 2010)
The electrical and optical properties of thermally evaporated titanyl phthalocyanine-β modification (TiOPc) thin films have been investigated. Thin films of TiOPc are prepared by thermal evaporation method on to glass substrates in high vacuum. Temperature dependence of electrical conductivity of the films is also investigated. The dependence of activation energy on post deposition annealing in air and in vacuum are studied. Annealing in air and vacuum decreases the intrinsic activation energy of TiOPc thin films. The optical absorption spectra of TiOPc thin films in the range 300-900 nm are recorded. The absorption spectra obtained in UV-Vis region for the as deposited and annealed films show two absorption bands namely the Q-band and the soret band. The fundamental and onset energy gaps are estimated. It is observed that air annealing and vacuum annealing have no significant role in the optical band gap of TiOPc thin films.